KONSEP FLOATING PLATFORM PADA RUMAH TINGGAL DI PANTAI MUTIARA, JAKARTA UTARA - Christevi Octavia, Jaclyn; Sufianto, Heru; Yatnawijaya S., Bambang (Jurnal Koridor, 2017)
Flood in flood prone area may degrades the quality of building materials, especially those made from timber and steel. Number of strategies for preventing flood have been implemented, including canal system, water dam, and infiltration affected region. This study seeks available modification of structural system implemented for individual residential building. The flood proof housing system was found to be effective installed in pantai mutiara housing area, North Jakarta. Some of supported materials has been choosen by consideration of materials weight, such as light steel as the main column, casco as the buoyancy system. This structural system modification concept also equipped by bump as the reservoir container of floodwater, and filtration tank to protect the whole system performance from dirt.